Use of English and English-Hiligaynon as media of instruction in teaching secondary general science - Ayoso, Jenifer Porras
The main purpose of this quasi-experimental research was to determine the effectiveness of the use of English and English-Hiligaynon as Media of Instruction in teaching General Science in the Secondary Level. It further assessed relationships and differences in the achievement of students based on students attitude in learning the subject, alongside other variables such as gender, and elementary grade in science. Participants of this study involved 72 freshmen students from Region VI, Division of Iloilo, specifically from the purposively chosen Barotac Nuevo National Comprehensive High School, Barotac Nuevo, Iloilo during the fourth quarter of the school-year 2007-2008. It involved two sections of first year students: Special Science Class (Control Group-English only), and the Regular Class (Experimental group-English-Hiligaynon). The same topics were taught for the two groups. The time allotment for each topic lasted for 1 hour and 20 minutes only. Topics were taken from the BSE-Department of Educations ready-made lesson plans for general science keeping the English text constant and focusing only on the media of instruction used. The data in the attitude of students in learning general science were gathered using the survey questionnaire and observation, which was designed and constructed by the teacher-researcher. The same set of test was administered in the pre-test and post test which was taken from the DepEds Unified Test in Science I. The t-test for independent sample was used in determining significant difference in the pre-test and the post test score between the control and experimental group. T-test for paired samples was utilized in determining the gain in score between the pre-test and post test scores for both groups. Analysis of Covariance (ANACOVA) was employed in further assessing the relationships and differences of other variables such as gender, elementary grade in science, and students attitude towards the subject to the achievement of students in science. The salient findings of the study were as follows: 1.) The difference in the Science mean scores between the pre-test and post test was highly significant for both groups (p<0.01) as both registered a significant improvement in the post test scores, though the gain in score of English-Hiligaynon group was relatively higher than the English-only group having obtained an increase of 2.84 and 2.46, respectively. Therefore, using both media made significant improvements in the Science achievement scores of the students but the English-Hiligaynon medium gave a higher gain than the English-only group which can be attributed to the fact that using the local dialect better facilitates the comprehension and develops better understanding among the students. 2.) The students Science post test scores is significantly influenced by the students elementary GPA in Science. The English-only group had a significantly higher Science GPA than the English Hiligaynon group, an indication that the students grade in Science significantly affects their achievement in Science. Students who got higher elementary grade in science tended to exhibit better achievement in General Science. 3.) The result of the achievement of students was significantly affected by gender. Female students obtained higher mean post test scores than the male students both between and within groups. 4.) The attitude of students toward science reflected no significant difference in their achievement in science. Both groups exhibit the same level of attitude towards learning science regardless of sex. On the basis of the aforementioned findings and conclusions, a replicate of similar study is suggested to validate the effect of English-Hiligaynon as medium of instruction in Science by observing same level of GPA in Science, the same special science section or similar gender, in a wider and larger scope and studies in other regional languages aside from Hiligaynon. Furthermore, promulgators and policy makers are even advised to re-consider orders and policies on restricting the language of instruction to English alone.